2013
DOI: 10.3727/096368912x658692
|View full text |Cite
|
Sign up to set email alerts
|

Allogenic Mesenchymal Stem Cell Transplantation Ameliorates Nephritis in Lupus Mice via Inhibition of B-Cell Activation

Abstract: Recent evidence indicates that bone marrow-derived mesenchymal stem cells (BM-MSCs) possess immunosuppressive properties both in vitro and in vivo. We have previously demonstrated that transplantation of human MSCs can significantly improve the autoimmune conditions in MRL/lpr mice. The current study aimed to determine the mechanisms by which murine BM-MSC transplantation (MSCT) ameliorates nephritis in MRL/lpr mice. In this study, we found that MSCT can significantly prolong the survival of MRL/lpr mice. Eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 47 publications
5
55
2
Order By: Relevance
“…Moreover, MSCs also could suppress the level of B-cell activating factor (BAFF) which secreted by dendritic cells in vitro. These results confirmed that allogenic MSCT could ameliorate the clinical symptoms in lupus mice, and the mechanism of suppressing the excessive activation of B cells via inhibiting BAFF production was also concordance with MSCs' immunomodulation property [9] . Other researches also indicated that MSCs exerted complex paracrine and endocrine actions including the secretion of growth factors and cytokines, modulation of immune response, antiapoptotic and anti-inflammatory effects, and so on.…”
Section: Research Highlightsupporting
confidence: 73%
“…Moreover, MSCs also could suppress the level of B-cell activating factor (BAFF) which secreted by dendritic cells in vitro. These results confirmed that allogenic MSCT could ameliorate the clinical symptoms in lupus mice, and the mechanism of suppressing the excessive activation of B cells via inhibiting BAFF production was also concordance with MSCs' immunomodulation property [9] . Other researches also indicated that MSCs exerted complex paracrine and endocrine actions including the secretion of growth factors and cytokines, modulation of immune response, antiapoptotic and anti-inflammatory effects, and so on.…”
Section: Research Highlightsupporting
confidence: 73%
“…An increase in peripheral regulatory T cells has been observed in successful (18) but also failed (43) MSC transplants in SLE patients, which makes the contribution of regulatory T cells to the MSC therapeutic effect in lupus inconclusive, whereas suppression or inhibition of the inflammatory subset of activated CD4 + CD25 + Foxp3 2 cells reported in murine (44) and human (45) lupus is effective in ameliorating some symptoms of disease. Allogeneic BALB/c MSC transfer has been reported to protected MRL/lpr mice from lupus nephritis by inhibiting B cell activation (46). To the contrary, we observed minimal effect of B6 MSC transfer on B cell activation or autoantibody production in our in vivo study, with the exception that B6 and not Sle1a1 MSCs decreased autoantibody production and the formation of B cell blasts in BWF1 mice.…”
Section: Discussioncontrasting
confidence: 51%
“…Likewise, MSCs suppressed the excessive activation of B cells and Th17 cells and restored regulatory T cells (Tregs), resulting in the amelioration of autoimmune disorders such as SLE [8][9][10]. Additionally, MSCs have been shown to modulate arthritis in mice via upregulating Tregs in peripheral blood and normalizing fibroblast-like synoviocytes, splenocyte proliferation, as well as cytokine secretion patterns [11,12].…”
Section: Clinical Ramification Of the Interaction Between Mscs And Admentioning
confidence: 97%